Preparation method of high-compaction lithium manganese iron phosphate positive electrode material
Through high-speed nano ball mill assisted secondary sintering method and carbon coating technology, the problems of conductivity and compaction density of lithium manganese iron phosphate positive electrode material are solved, and the efficient conductivity and good compaction density of the material are achieved while reducing the specific surface area.
Patent Information
- Application Number
- CN202411943451.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Due to the introduction of manganese element, lithium manganese iron phosphate positive electrode material has reduced conductivity and reduced powder compaction density. Although existing modification methods such as nanoification and carbon coating can improve porosity and powder compaction gauge change, it is difficult to maintain the high-efficiency conductivity and good compaction density of the material at the same time.
The manganese phosphate positive electrode material is synthesized by high-speed nano ball mill assisted secondary sintering. The void ratio is reduced through secondary grinding and secondary sintering, and a carbon source is added during the sintering process to achieve good carbon coating.
It effectively improves the powder compaction density and conductivity of the material, while reducing the specific surface area, and maintaining the efficient electrochemical performance of the material.
Smart Images

Figure CN119786544A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium iron manganese phosphate positive electrode materials, and in particular relates to a preparation method of a high-density lithium iron manganese phosphate positive electrode material. Background Art
[0002] Lithium iron manganese phosphate (LiMn x Fe 1-x PO 4 ) is in lithium iron phosphate (LiFePO 4 ) is doped with a certain proportion of manganese (Mn) on the basis of phosphate-based lithium-ion battery positive electrode material. Through the doping of manganese, on the one hand, the advantages of iron and manganese can be effectively combined, and on the other hand, manganese and iron are located in the fourth period subgroup and adjacent in the periodic table, with similar ionic radius and some chemical properties, so doping will not significantly affect the original structure. And the Mn element can increase the voltage platform, thereby increasing the energy density of the iron-lithium system. LMFP maintains the stable olivine structure of LFP and introduces the high-voltage platform LMP, thereby improving the energy density of the iron-lithium system.
[0003] However, the introduction of manganese will reduce the overall conductivity and the powder compaction density. To address the disadvantage of poor conductivity, current modification methods include nano-materials, bulk doping, and surface carbon coating. These are also one of the reasons for the increase in porosity of lithium manganese iron phosphate materials and the increase in powder compaction density.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] Based on the problems existing in the background technology, the present invention provides a method of synthesizing manganese phosphate positive electrode material by using high-speed nano ball milling assisted by secondary sintering, which can effectively reduce the porosity and achieve good carbon coating through secondary grinding and secondary sintering.
[0006] The present invention is implemented by the following technical solutions:
[0007] A method for preparing a high-density lithium manganese iron phosphate positive electrode material comprises the following steps:
[0008] (1) placing a manganese source, an iron source, and a phosphorus source in deionized water to obtain a slurry 1, stirring, high-speed ball milling, and constant temperature water bath, adding an oxidant, stirring and oxidizing, and then drying the slurry to obtain a manganese iron phosphate precursor powder;
[0009] (2) sintering the ferromanganese phosphate precursor powder once to obtain a ferromanganese phosphate sintered material;
[0010] (3) placing the ferromanganese phosphate 1 sintered material in deionized water, adding a lithium source and a carbon source at the same time to obtain a slurry 2, stirring, secondary high-speed ball milling and drying to obtain a lithium ferromanganese phosphate precursor powder;
[0011] (4) The lithium manganese iron phosphate precursor powder is subjected to secondary sintering to obtain a high-density lithium manganese iron phosphate positive electrode material.
[0012] The present invention synthesizes lithium iron manganese phosphate positive electrode material by means of secondary grinding, secondary sintering and adding carbon coating. The two grinding and sintering can well mix the two phases of manganese iron and iron uniformly. At the same time, since the valence state of manganese iron has been oxidized to positive trivalent and positive tetravalent before the first sintering, and there is no carbon source, no reduction reaction will occur during the first sintering to limit the growth of crystals, and manganese iron phosphate with a large crystal volume can be obtained, which is conducive to improving the final powder compaction of lithium iron manganese phosphate. During the second grinding and sintering, the added carbon source can be well distributed on the surface of the solid particles when drying to form a good and uniform coating layer. The secondary grinding can eliminate the void gaps generated during the first sintering process, further improve the compaction density of the powder, and reduce the specific surface area.
[0013] Furthermore, the molar ratio of lithium, manganese, iron and phosphorus used in the lithium manganese iron phosphate positive electrode material is x:y:(1-y):z, wherein 1≤x≤1.1, 0.1≤y≤0.9, and 1≤z≤1.05.
[0014] Furthermore, the manganese source is one or more of manganese tetraoxide, manganese dioxide, manganese carbonate, manganese monoxide, and manganese iron oxide;
[0015] The iron source is one or more of ferric phosphate, ferric dioxide, ferric tetroxide, ferrous oxalate, ferrous phosphate, and ferromanganese oxide;
[0016] The phosphorus source is one or more of iron phosphate, phosphoric acid, lithium dihydrogen phosphate, lithium phosphate or monoammonium phosphate;
[0017] The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium sulfate or lithium oxalate;
[0018] The oxidizing agent is hydrogen peroxide.
[0019] Furthermore, in step (1) and step (3), the solid content of slurry 1 and slurry 2 is 25-45wt%;
[0020] The stirring speed is 420-540 rpm;
[0021] The drying is carried out by spray drying, and the air inlet temperature of the spray drying is not less than 220°C, and the air outlet temperature is not less than 90°C.
[0022] Furthermore, in step (1), the temperature of the constant temperature water bath is 60-80° C. and the time is 6-10 h.
[0023] Furthermore, in step (1), the rotation speed of the first high-speed ball mill is 2100-3000 rpm, and the D50 average particle size of the mixed slurry obtained after the first high-speed ball mill is 100-500 nm.
[0024] Furthermore, in step (2), the primary sintering temperature is 420-620° C., and the sintering time is 3-20 hours in an air atmosphere.
[0025] Furthermore, in step (3), the rotation speed of the secondary high-speed ball milling is 2100-3000 rpm, and the D50 average particle size of the mixed slurry obtained after the secondary high-speed ball milling is 100-600 nm.
[0026] Furthermore, in step (4), the secondary sintering temperature is 600-850° C., and the sintering is carried out in a nitrogen atmosphere for 5-20 hours.
[0027] Furthermore, in step (3), the amount of carbon source added is 6-18% of the theoretical mass of lithium manganese iron phosphate generated;
[0028] The carbon source is one or more of glucose, lactose, sucrose, polyvinyl alcohol, phenolic resin, epoxy resin and ascorbic acid.
[0029] Beneficial effects of the present invention:
[0030] The present invention provides a method for synthesizing manganese phosphate positive electrode materials by using high-speed nano-ball milling assisted secondary sintering, which can reduce the porosity and achieve good carbon coating by secondary grinding and secondary sintering. Compared with other existing technologies, it can improve the powder compaction density of the material while maintaining a good capacity, improve the conductivity and effectively reduce the specific surface area of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0032] Figure 1 This is a SEM image of the lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0033] Figure 2 This is a SEM image of the lithium manganese iron phosphate positive electrode material prepared in Example 2 of the present invention;
[0034] Figure 3 Graph showing particle size distribution of lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in more complete and detailed manner in conjunction with the accompanying drawings and implementation cases. It should be noted that the implementation cases described are only part of the embodiments of the present invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] This embodiment provides a preparation process of a lithium manganese iron phosphate positive electrode material, and the specific steps are as follows:
[0038] (1) Manganese tetraoxide, ferric iron tetraoxide and phosphoric acid were placed in deionized water according to the main element molar ratio of Mn:Fe:P=0.4:0.6:1.03 to form a solid-liquid mixed phase with a solid content of 40%. After stirring at 480 rpm and high-speed ball milling at 2700 rpm for 1 hour, the particle size D50 was measured to be evenly distributed at 400 nm. The mixture was then placed in a 70° C. constant temperature water bath for 6 hours. A certain amount of oxidant was then added for oxidation and the temperature was maintained at 70° C. and stirred for 1 hour to completely oxidize the mixture. The slurry was then dried in a spray dryer at 240° C. to obtain a manganese iron phosphate precursor powder.
[0039] (2) calcining the ferromanganese phosphate precursor powder obtained in step (1) in a tube furnace at 500° C. in an air atmosphere for 10 hours to obtain a ferromanganese phosphate calcined material;
[0040] (3) the ferromanganese phosphate prepared in step (2) is further placed in deionized water to form a slurry with a solid content of 35%, and lithium carbonate and ferromanganese phosphate are added at a molar ratio of Li:P=1.03:1, and the carbon source is glucose of 10% of the theoretical mass of the generated lithium ferromanganese phosphate. The mixture is stirred again at a frequency of 420 rpm and high-speed ball milled at a speed of 2700 rpm for 0.5 hours. The particle size D50 is measured to be averagely distributed at 500 nm. The slurry is completely dried in a spray dryer at 240°C to finally obtain a lithium ferromanganese phosphate precursor;
[0041] (4) The lithium manganese iron phosphate precursor prepared in step (3) is placed in a tubular furnace at 700° C. and in a nitrogen atmosphere for 10 hours, and then naturally cooled to obtain a lithium manganese iron phosphate positive electrode material.
[0042] Example 2
[0043] This embodiment provides a preparation process of a lithium manganese iron phosphate positive electrode material, and the specific steps are as follows:
[0044] (1) Manganese tetraoxide, ferric tetraoxide and phosphoric acid were placed in deionized water according to the element molar ratio of Mn:Fe:P=0.6:0.4:1.04 to form a solid-liquid mixed phase with a solid content of 35%. After stirring at 480 rpm and high-speed ball milling at 2700 rpm for 1.5 hours, the particle size D50 was measured to be averagely distributed at 350 nm. Then, the mixture was placed in a constant temperature water bath at 80°C for 8 hours, and then a certain amount of oxidant was added for oxidation and the temperature was maintained at 80°C and stirred for 1 hour to completely oxidize. Then, the slurry was dried in a spray dryer at 240°C to finally obtain a manganese iron phosphate precursor powder;
[0045] (2) calcining the ferromanganese phosphate precursor powder obtained in step (1) in a tube furnace at 480° C. in an air atmosphere for 15 hours to obtain a ferromanganese phosphate calcined material;
[0046] (3) the ferromanganese phosphate prepared in step (2) is further placed in deionized water to form a slurry with a solid content of 35%, and lithium carbonate and ferromanganese phosphate are added at a molar ratio of Li:P=1.04:1, and the carbon source is glucose of 12% of the theoretical mass of the generated lithium ferromanganese phosphate. The mixture is stirred again at a frequency of 420 rpm and high-speed ball milled at a speed of 2700 rpm for 0.5 hours. The particle size D50 is measured to be averagely distributed at 450 nm. The slurry is completely dried in a spray dryer at 240°C to finally obtain a lithium ferromanganese phosphate precursor;
[0047] (4) The lithium manganese iron phosphate precursor prepared in step (3) is sintered in a tubular furnace at 740° C. in a nitrogen atmosphere for 12 hours, and then naturally cooled to obtain a lithium manganese iron phosphate positive electrode material.
[0048] Example 3
[0049] This embodiment provides a preparation process of a lithium manganese iron phosphate positive electrode material, and the specific steps are as follows:
[0050] (1) manganese dioxide, ferrous oxalate and phosphoric acid with a main element molar ratio of Mn:Fe:P=0.6:0.4:1.04 were placed in deionized water to form a solid-liquid mixed phase with a solid content of 35%. After stirring at 480 rpm and high-speed ball milling at 2700 rpm for 1 hour, the particle size D50 was measured to be averagely distributed at 450 nm, and then placed in a 70° C. constant temperature water bath for 6 hours, and then a certain amount of oxidant was added for oxidation and the temperature was maintained at 70° C. and stirred for 1 hour to completely oxidize. Then the slurry was dried in a spray dryer at 240° C. to finally obtain a manganese iron phosphate precursor powder;
[0051] (2) calcining the ferromanganese phosphate precursor powder obtained in step (1) in a tube furnace at 520° C. in an air atmosphere for 10 hours to obtain a ferromanganese phosphate calcined material;
[0052] (3) the ferromanganese phosphate prepared in step (2) is further placed in deionized water to form a slurry with a solid content of 35%, and lithium carbonate and ferromanganese phosphate are added at a molar ratio of Li:P=1.04:1, and the carbon source is sucrose of 10% of the theoretical mass of lithium ferromanganese phosphate generated, and the mixture is stirred again at a frequency of 420 rpm and high-speed ball milled at a speed of 2700 rpm for 0.5 hours. The particle size D50 is measured to be averagely distributed at 500 nm, and the slurry is completely dried in a spray dryer at 240°C to finally obtain a lithium ferromanganese phosphate precursor;
[0053] (4) The lithium manganese iron phosphate precursor prepared in step (3) is placed in a tubular furnace at 700° C. and in a nitrogen atmosphere for 14 hours, and then naturally cooled to obtain a lithium manganese iron phosphate positive electrode material.
[0054] The lithium manganese iron phosphate positive electrode materials prepared in Example 1 and Example 2 were analyzed to obtain Figures 1 to 3 According to the content shown. Figures 1 to 3 The following conclusions can be drawn: the lithium manganese iron phosphate positive electrode material prepared in Example 1 and Example 2 has clear particle boundaries and good crystallinity, and no fibrous carbon and fine particles appear on the surface, indicating that the carbon coating effect is good, which is a good proof of the small specific surface area of the material, and can improve the conductivity and bring good electrochemical performance. The secondary grinding can obtain such size-graded particles, which is also a factor in improving the powder compaction density of the material.
[0055] Comparative Example 1
[0056] The comparative example 1 is basically the same as the example 1, except that the ferromanganese phosphate precursor is not completely oxidized during preparation. The specific steps are as follows:
[0057] (1) manganese tetraoxide, ferromanganese tetraoxide and phosphoric acid were placed in deionized water according to the main element molar ratio of Mn:Fe:P=0.4:0.6:1.03 to form a solid-liquid mixed phase with a solid content of 40%. After stirring at 480 rpm and high-speed ball milling at 2700 rpm for 1 hour, the particle size D50 was measured to be averagely distributed at 400 nm. The mixture was then placed in a constant temperature water bath at 70°C for 6 hours. The slurry was then dried in a spray dryer at 240°C to finally obtain a manganese iron phosphate precursor powder.
[0058] (2) calcining the ferromanganese phosphate precursor powder obtained in step (1) in a tube furnace at 500° C. in an air atmosphere for 10 hours to obtain a ferromanganese phosphate calcined material;
[0059] (3) the ferromanganese phosphate prepared in step (2) is further placed in deionized water to form a slurry with a solid content of 35%, and lithium carbonate and ferromanganese phosphate are added at a molar ratio of Li:P=1.03:1, and the carbon source is glucose of 10% of the theoretical mass of the generated lithium ferromanganese phosphate. The mixture is stirred again at a frequency of 420 rpm, and high-speed ball milling is performed at a frequency of 2700 rpm for 0.5 hours. The particle size D50 is measured to be averagely distributed at 500 nm. The slurry is completely dried in a spray dryer at 240°C to finally obtain a lithium ferromanganese phosphate precursor;
[0060] (4) The lithium manganese iron phosphate precursor prepared in step (3) is placed in a tubular furnace at 700° C. and in a nitrogen atmosphere for 10 hours, and then naturally cooled to obtain a lithium manganese iron phosphate positive electrode material.
[0061] Comparative Example 2
[0062] This comparative example 2 is basically the same as Example 1, except that the lithium source is added in step (1). The specific steps are as follows:
[0063] (1) lithium carbonate, manganese tetraoxide, ferromanganese tetraoxide, and phosphoric acid were placed in deionized water according to the main element molar ratio of Li:Mn:Fe:P=1.06:0.4:0.6:1.03 to form a solid-liquid mixed phase with a solid content of 40%. After stirring at 480 rpm and high-speed ball milling at 2700 rpm for 1 hour, the particle size D50 was measured to be averagely distributed at 400 nm. The mixture was then placed in a constant temperature water bath at 70°C for 6 hours. The slurry was then dried in a spray dryer at 240°C to finally obtain a manganese iron phosphate precursor powder.
[0064] (2) calcining the ferromanganese phosphate precursor powder obtained in step (1) in a tube furnace at 500° C. in an air atmosphere for 10 hours to obtain lithium ferromanganese phosphate calcined material;
[0065] (3) The lithium iron manganese phosphate calcined material prepared in step (2) is further placed in deionized water to form a slurry with a solid content of 35%, and the carbon source added is glucose of 10% of the theoretical mass of the generated lithium iron manganese phosphate. The mixture is stirred again at a frequency of 420 rpm, and high-speed ball milling is performed at a frequency of 2700 rpm for 0.5 hours. The particle size D50 is measured to be averagely distributed at 500 nm. The slurry is completely dried in a spray dryer at 240° C. to finally obtain a lithium iron manganese phosphate precursor;
[0066] (4) The lithium manganese iron phosphate precursor prepared in step (3) is placed in a tubular furnace at 700° C. and in a nitrogen atmosphere for 10 hours, and then naturally cooled to obtain a lithium manganese iron phosphate positive electrode material.
[0067] As shown in Table 1, there is a comparison of the electrochemical properties, powder compaction, specific surface area and other data of five groups of samples in Examples 1-3 and Comparative Examples 1-2. It can be seen from Table 1 that the lithium manganese iron phosphate positive electrode material prepared by the invention has good electrochemical properties, higher powder compaction density and lower surface area.
[0068] Table 1
[0069]
[0070] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For ordinary technicians in this field, any modifications, equivalent substitutions, improvements, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A method for preparing a high-density lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: (1) placing a manganese source, an iron source, and a phosphorus source in deionized water to obtain a slurry 1, stirring, high-speed ball milling, and constant temperature water bath, adding an oxidant, stirring and oxidizing, and then drying the slurry to obtain a manganese iron phosphate precursor powder; (2) sintering the ferromanganese phosphate precursor powder once to obtain a ferromanganese phosphate sintered material; (3) placing the ferromanganese phosphate 1 sintered material in deionized water, adding a lithium source and a carbon source at the same time to obtain a slurry 2, stirring, secondary high-speed ball milling and drying to obtain a lithium ferromanganese phosphate precursor powder; (4) The lithium manganese iron phosphate precursor powder is subjected to secondary sintering to obtain a high-density lithium manganese iron phosphate positive electrode material.
2. The method for preparing the high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of lithium, manganese, iron and phosphorus used in the lithium iron manganese phosphate positive electrode material is x:y:(1-y):z, wherein 1≤x≤1.1, 0.1≤y≤0.9, and 1≤z≤1.
05.
3. The method for preparing the high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The manganese source is one or more of manganese tetraoxide, manganese dioxide, manganese carbonate, manganese monoxide, and manganese iron oxide; The iron source is one or more of ferric phosphate, ferric dioxide, ferric tetroxide, ferrous oxalate, ferrous phosphate, and ferromanganese oxide; The phosphorus source is one or more of iron phosphate, phosphoric acid, lithium dihydrogen phosphate, lithium phosphate or monoammonium phosphate; The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium sulfate or lithium oxalate; The oxidizing agent is hydrogen peroxide.
4. The method for preparing a high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (1) and step (3), the solid content of slurry 1 and slurry 2 is 25-45wt%; The stirring speed is 420-540 rpm; The drying is carried out by spray drying, and the inlet air temperature of the spray drying is not less than 220°C, and the outlet air temperature is not less than 90°C.
5. The method for preparing the high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (1), the temperature of the constant temperature water bath is 60-80° C. and the time is 6-10 hours.
6. The method for preparing a high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (1), the rotation speed of the first high-speed ball mill is 2100-3000 rpm, and the D50 average particle size of the mixed slurry obtained after the first high-speed ball mill is 100-500 nm.
7. The method for preparing a high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (2), the primary sintering temperature is 420-620° C., and the sintering is carried out in an air atmosphere for 3-20 hours.
8. The method for preparing a high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (3), the rotation speed of the secondary high-speed ball milling is 2100-3000 rpm, and the D50 average particle size of the mixed slurry obtained after the secondary high-speed ball milling is 100-600 nm.
9. The method for preparing a high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (4), the secondary sintering temperature is 600-850° C., and the sintering is performed in a nitrogen atmosphere for 5-20 hours.
10. The method for preparing a high-density lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (3), the amount of carbon source added is 6-18% of the theoretical mass of lithium manganese iron phosphate generated; The carbon source is one or more of glucose, lactose, sucrose, polyvinyl alcohol, phenolic resin, epoxy resin and ascorbic acid.
Citation Information
Patent Citations
Method for preparing carbon-clad lithium iron manganese phosphate material through two-step calcination
CN105762335A
Method for preparing nanoscale lithium ferric manganese phosphate material by using co-crystallization method
CN113659134A
Carbon-coated lithium manganese iron phosphate composite material and preparation method thereof
CN114620703A
Preparation method of multi-carbon-coated high-compaction lithium manganese iron phosphate
CN115231543A
Lithium manganese iron phosphate positive electrode material and application thereof
CN116534828A
Cited By
Composite lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN120288739A
Modified monocrystal lithium iron manganese phosphate positive electrode material and preparation method and application thereof
CN120400972A
Method for preparing high-compaction lithium manganese iron phosphate positive electrode material
CN121573663A
Preparation method of ferromanganese phosphate precursor and preparation method of lithium ferromanganese phosphate positive electrode material
CN121717351A
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN121823504A